Spirometry in Central Asian Lowlanders and Highlanders, a Population Based Study - Ulrich, Stefanie; Furian, Michael; Estebesova, Bermet; Toktogulova, Nurgul; Beishekeeva, Gulnara; Ulrich, Silvia; Burney, Peter G. J.; Sooronbaev, Talant M.; Bloch, Konrad E. (Frontiers in Medicine, 2020)
Introduction: The purpose of the study was to establish spirometric reference values for a Central Asian population of highlanders and lowlanders. Methods: Spirometries from a population-based cross-sectional study performed in 2013 in rural areas of Kyrgyzstan were analyzed. Using multivariable linear regression, Global Lung Function Initiative (GLI) equations were fitted separately for men and women, and altitude of residence (700-800m, 1900-2800m) to data from healthy, never-smoking Kyrgyz adults. The general GLI equation was applied: predicted value=exp(a0+a1*ln(height)+a2*ln(age)+b1*(age/100)+b2*(age/100)^2+b3*(age/100)^3+b4*(age/100)^4+b5*(age/100)^5). Results: Of 2784 screened Kyrgyz, 448 healthy, non-smoking highlanders (379 females) and 505 lowlanders (368 females), aged 18 to 91 years, were included. Predicted FVC in Kyrgyz fit best with GLI “North-East Asians”, predicted FEV1 fit best with GLI “Other/Mixed”. Predicted FEV1/FVC was lower than that of all GLI categories. Age- and sex-adjusted mean FVC and FEV1 were higher in highlanders (+0.138l, +0.132l) than in lowlanders (P<0.001, all comparisons), but FEV1/FVC was similar. Conclusion: We established prediction equations for an adult Central Asian population indicating that FVC is similar to GLI “North-East Asian” and FEV1/FVC is lower than in all other GLI population categories, consistent with a relatively smaller airway caliber. Central Asian highlanders have significantly greater dynamic lung volumes compared to lowlanders which may be due to environmental and various other effects.